Flow and spawning habitat relationships for Dolly Varden: Understanding habitat–population dynamics in the Canadian Western Arctic. (4th December 2019) - Mochnacz, Neil J.; Ghamry, Haitham K.; Enders, Eva C.; Watkinson, Douglas A.; Gallagher, Colin P.; Reist, James D.
Abstract: Northern form Dolly Varden ( Salvelinus malma malma ) have been designated as a species of Special Concern in Canada due to declines in population abundance and potential threats. Concern over detrimental effects of low flows on population abundance prompted research on how variability in discharge regimes influence habitat availability. Habitat suitability indices for prespawning and spawning adult anadromous Dolly Varden from two streams were integrated into a two‐dimensional hydrodynamic habitat model to assess the effect of flow variability on usable habitat. Regional hydrographs were used to identify an ecologically relevant range of flows that provided optimal spawning habitat for these populations and examine the relationship between abundance and discharge. Adults spawned in the tail end of pools at moderate water depths and water velocities, and used pebble‐ to cobble‐sized substrate for building redds; whereas, prespawning adults occupied deeper pools with moderate velocities and used cobble for cover. Model outputs showed that spawning habitat availability was optimized at flow rates between 1.6 and 3.0 m 3 /s and between 1.0 and 6.0 m 3 /s in Fish Hole Creek (FHC) and Little Fish Creek, respectively. A positive relationship between flows during the fall spawning period and abundance of the FHC population suggests that higher flows coinciding with optimal habitat availability may have contributed to positive recruitment. To strengthen and refine this habitat–population relationship for Dolly Varden in this area requires investigation of a broader suite of variables associated with environmental regimes and physical habitat in reaches used for spawning.